2019
DOI: 10.1080/19476337.2018.1553895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germination time on the antioxidant properties of edible seeds

Abstract: The aim of this study was to determine the level of antioxidants in the seeds of wheat, lentil, pea, radish, broccoli, alfalfa, sunflower and amaranth germinated for 24, 72 and 120 hours. Following germination, the highest increases in the total phenols corresponded to 5.39, 4.62 and 2.20 times in broccoli, radish and alfalfa seeds respectively. The 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity was higher after germination for 120 hours in all the seed types as compared with the non-germinated seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
5
20
1
Order By: Relevance
“…In the broccoli seeds it fluctuated after 12 h both in darkness and in the light from 6.2±0.19 mmol TE 100 g -1 DW to 31.96± 1.54 mmol TE 100g -1 DW after 24 h in the light. This is in line with the data from scientific literature that germinated Cruciferous seeds have higher scavenging activity compared to un-germinated (Zielinski et al, 2007;Taraseviciene et al, 2019 Note: the values marked with different letters for each seed type represent significant differences between values (P < 0.05).…”
Section: Scavenging Activity (Sa)supporting
confidence: 89%
See 1 more Smart Citation
“…In the broccoli seeds it fluctuated after 12 h both in darkness and in the light from 6.2±0.19 mmol TE 100 g -1 DW to 31.96± 1.54 mmol TE 100g -1 DW after 24 h in the light. This is in line with the data from scientific literature that germinated Cruciferous seeds have higher scavenging activity compared to un-germinated (Zielinski et al, 2007;Taraseviciene et al, 2019 Note: the values marked with different letters for each seed type represent significant differences between values (P < 0.05).…”
Section: Scavenging Activity (Sa)supporting
confidence: 89%
“…Seeds analysed by germination in light and dark scavenging activity significantly increase at similar positions within the error limits in broccoli seeds from 24 h -48 h compared to the control sample and germination after 12 h. In turn, the scavenging activity of radish seeds increases already after 12 h germination in comparison with the control sample. It is similar to the results of other researchers that the germination of sprouted broccoli and radishes is higher than that of un-germinated seeds (Zielinski et al, 2007;Taraseviciene et al, 2019). Scavenging activity was reduced significantly in the hemp seeds after 36 hours germination in the light compared to the control sample, which may be related to freely soluble phenols that have not decomposed at this stage of the polymerization process (Perez-Balibrea, Moreno, & Garcia-Viguera, 2008).…”
Section: Controlsupporting
confidence: 89%
“…Germination results in a higher nutritional and functional value associated with the quality and quantity of nutrients, biologically active compounds, and antioxidant potential (Cornejo et al, 2015). Tarasevicˇiene _ et al (2019) found that the level of alpha-tocopherol in germinated wheat grains was 5.3 times higher than in non-germinated grains.…”
Section: Chemical Characteristicsmentioning
confidence: 99%
“…Germination is a simple, inexpensive, and environmentally friendly method of producing plant foods with functional properties. Germination reduces the level of antinutrients, increases the nutritional and medicinal properties of food, and induces the accumulation of secondary metabolites, some of which have been characterized as antioxidants (Aguilera et al., 2013; Tarasevičien ė et al., 2019). Germination promotes the accumulation of phenolic acids, flavonoids, and vitamins, which are health promoters and therefore increase grain value (Oh and Rajashekar, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation